A multi-site survey of forensic nursing assessment. Issue 2 (22nd May 2019) - Walker, Helen; Tulloch, Lindsay; Boa, Karen; Ritchie, Gordon; Thompson, John
Abstract : Purpose: A major difficulty identified many years ago in psychiatric care is the shortage of appropriate instruments with which to carry out valid and reliable therapeutic assessments which are behaviourally based and therefore appropriate for use in a variety of contexts. The aim of this project was to ascertain the utility of a forensic nursing risk assessment tool - Behavioural Status Index (BEST-Index). The paper aims to discuss these issues. Design/methodology/approach: A multi-site cross-sectional survey was undertaken using mixed method design. Quantitative data was generated using BEST-Index to allow comparisons across three different levels of security (high, medium and low) in Scotland and Ireland. Qualitative data were gathered from patients and multi-disciplinary team (MDT) members using semi-structured interviews and questionnaire. Findings: Measured over an 18-month period, there was a statistically significant improvement in behaviour, when comparing patients in high and medium secure hospitals. Two key themes emerged from patient and staff perspectives: "acceptance of the process" and "production and delivery of information", respectively. The wider MDT acknowledge the value of nursing risk assessment, but require adequate information to enable them to interpret findings. Collaborating with patients to undertake risk assessments can enhance future care planning. Research limitations/implications: Studies using cross-section can only provide information at fixed points in time. Practical implications: The BEST-Index assessment tool is well established in clinical practice and has demonstrated good utility. Originality/value: This project has served to highlight the unique contribution of BEST-Index to both staff and patients alike and confirm its robustness and versatility across differing levels of security in Scottish and Irish forensic mental health services.